1964
DOI: 10.1071/bi9640892
|View full text |Cite
|
Sign up to set email alerts
|

Properties of An Iridescent Virus From the Beetle, Serioesthis Pruinosa

Abstract: The recently described iridescent virus from Serice8this (SIV) is closely related to Tipula iridescent virus (TIV). TIV and SIV are morphologically similar and have similar sedimentation coefficients (820, w = 2200 S). SIV differs from TIV serologically and in DNA content. Large yields of purified SIV, of the order of 2 mg virus protein per pupa, maybe obtained from the wax moth, Galleria melloneUa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
3

Year Published

1966
1966
2000
2000

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(32 citation statements)
references
References 12 publications
0
29
3
Order By: Relevance
“…From the epidemiological viewpoint further work on thermal inactivation of SIV in soil is required. We already know that SIV that has been thoroughly dried over phosphorus pentoxide will withstand heating to 80°0 for 3 hr, but the virus in the presence of water, and especially in the presence of Mg2+, is more sensitive to thermal inactivation (Day and Mercer 1964).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the epidemiological viewpoint further work on thermal inactivation of SIV in soil is required. We already know that SIV that has been thoroughly dried over phosphorus pentoxide will withstand heating to 80°0 for 3 hr, but the virus in the presence of water, and especially in the presence of Mg2+, is more sensitive to thermal inactivation (Day and Mercer 1964).…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of the virus used have been described (Day and Mercer 1964). Viral concentration was estimated on purified preparations by measuring absorbance at 260 m"", in a Beckman DU spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) Immunity mechanisms of the host may destroy or inhibit some otherwise infectious particles. Day and Mercer (1964) reported that the total particle/infectious particle ratio of SIV was not greater than 10: 1, but the experiments were based on tenfold dilutions, and the question has therefore been examined more closely.…”
mentioning
confidence: 99%
“…Virus was prepared from infected Galleria mellonel"la larvae by centrifugation in buffer and in a sucrose density gradient (Day and Mercer 1964). SIV is unusually easy to purify, and no special precautions to overcome problems of contamination are necessary.…”
mentioning
confidence: 99%